Новый вид гологлаза — Ablepharus lindbergi sp. n. (Reptilia, Sauria, Scincidae) из Афганистана. - Еремченко, В.К.; Щербак, Н.Н. (Вестник зоологии, 1980)
The paper is concerned with a description of the new snake-eyed lizard species Ablepharus lindbergi from Western Afghanistan which was previously attributed to A. bivittatus as a subspecies. The new species differs from A. bivittatus by 6 longitudinal rows of scale, 26 rows of scale around the body middle, increased scutella on antebra- chium and isolated area of distribution